Developing and validating a business simulation systems success model in the context of management education. Issue 2 (July 2022) - Wei, Chung-Lun; Wang, Yu-Min; Lin, Hsin-Hui; Wang, Yi-Shun; Huang, Jun-Lin
Abstract: Business simulation game systems (BSGs) have become an important learning tool for higher education in business and management fields in recent years. However, few studies have investigated how BSG systems affect perceived learning effectiveness and entrepreneurial self-efficacy (ESE). Based on the previous information systems literature, this study developed and validated a BSG systems success model. The newly proposed success variable of model-reality fit, which was conceptualized as the fit between the BSG model and the real-world business environment, was also examined. Data collected from 152 college students in Taiwan was tested against the research model using the partial least squares (PLS) approach. The results indicate that system quality and model-reality fit positively influence user satisfaction, which in turn promotes reuse intention, learning effectiveness, and ESE, while service quality and information quality do not. Furthermore, service quality and model-reality fit play a critical role in determining reuse intention, although system quality and information quality do not have a significant effect on reuse intention. Other than the insignificant impact of user satisfaction on ESE, the results also confirm that user satisfaction and reuse intention positively predict learning effectiveness and ESE. Highlights: We develop and validate a business simulation systems success model. System quality positively influences user satisfaction. User satisfaction promotes reuse intention, learning effectiveness, and entrepreneurial self-efficacy directly or indirectly. Service quality plays a critical role in determining reuse intention. Model-reality fit positively affects both user satisfaction and reuse intention.